If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -7(2 + -1x) = 5k + 2(-2 + -4x) 3 + (2 * -7 + -1x * -7) = 5k + 2(-2 + -4x) 3 + (-14 + 7x) = 5k + 2(-2 + -4x) Combine like terms: 3 + -14 = -11 -11 + 7x = 5k + 2(-2 + -4x) -11 + 7x = 5k + (-2 * 2 + -4x * 2) -11 + 7x = 5k + (-4 + -8x) Reorder the terms: -11 + 7x = -4 + 5k + -8x Solving -11 + 7x = -4 + 5k + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -11 + 7x + 8x = -4 + 5k + -8x + 8x Combine like terms: 7x + 8x = 15x -11 + 15x = -4 + 5k + -8x + 8x Combine like terms: -8x + 8x = 0 -11 + 15x = -4 + 5k + 0 -11 + 15x = -4 + 5k Add '11' to each side of the equation. -11 + 11 + 15x = -4 + 11 + 5k Combine like terms: -11 + 11 = 0 0 + 15x = -4 + 11 + 5k 15x = -4 + 11 + 5k Combine like terms: -4 + 11 = 7 15x = 7 + 5k Divide each side by '15'. x = 0.4666666667 + 0.3333333333k Simplifying x = 0.4666666667 + 0.3333333333k
| 35+2x=58 | | 8x-8=6x+28 | | 8a+3-5a-2a= | | (X-1)+5+x=12 | | 2g+4=24 | | 5.7+6.6= | | (7x+15)=(10-9) | | 36x=8-14p | | 3=17-7n | | 14=4(7-8p)-6(4p-7) | | 250+14(h)=22(h) | | -y+3-3=-6 | | 5(2x-3)=7x+15 | | 11x-15=40 | | 3f-12=3(f+12) | | 5.25+15=46.50 | | 8x-3=3x-7 | | -4r+4r=8-4r+3r | | 130+40c=270 | | 4b-11=5 | | 15x-54=66 | | 3t^2-14t-22=0 | | (4x-1)(2x^2+3)= | | 64x^2-644x+1552=0 | | -6x+3=-39 | | .3x+5=6 | | k+9=6(k-1) | | 49=(-9y)-68 | | 130+40c=130 | | 3(4x^2-49)=27 | | 2-3x=x+y+2 | | 2+3ln(x+1)=4 |